(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2014)
Back ground: Type 2 Diabetes mellitus is state of uncompensated insulin resistance. But what actually predisposes to it, is still a controversy. Obesity is often marked as a precondition for such insulin resistance. But the degree of association and mode of pathogenesis are grossly debated. Methods: Here we explored the correlation of physical parameters for obesity like BMI (Body Mass Index), abdominal circumference, waist- hip ratio and the adipocytokines like leptin and adiponectin with the degree of insulin resistance (HOMA-IR score) in 167 patients of type 2 Diabetes mellitus. Result: We found significant positive correlation between BMI, abdominal circumference, waist- hip ratio and insulin resistance. Leptin showed significant positive correlation with all the said physical parameters. But, adiponectin showed a negative correlation with abdominal circumference, waist- hip ratio and fasting insulin. Leptin- adiponectin ratio showed a significant positive correlation with insulin resistance. Conclusion: Leptin shoots up with increased adiposity where as adiponectin gets reduced in central obesity which may contribute to insulin resistance. Though neither of leptin and adiponectin showed any significant correlation with insulin resistance individually, a significant positive correlation was found between leptin and adiponectin ratio and HOMA IR score. Therefore, the ratio can be an authentic predictor of insulin resistance as it takes into account the interplay of both of the adipocytokines for its causation. DOI: http://dx.doi.org/10.3329/bjpp.v30i1.20791 Bangladesh J Physiol Pharmacol 2014; 30(1):29-32